A protein trap strategy to detect GFP-tagged proteins expressed from their endogenous loci in Drosophila - Morin, Xavier (The National Academy of Sciences, 2001)
In Drosophila, enhancer trap strategies allow rapid access to expression patterns, molecular data, and mutations in trapped genes. However, they do not give any information at the protein level, e.g., about the protein subcellular localization. Using the green fluorescent protein (GFP) as a mobile artificial exon carried by a transposable P-element, we have developed a protein trap system. We screened for individual flies, in which GFP tags full-length endogenous proteins expressed from their endogenous locus, allowing us to observe their cellular and subcellular distribution. GFP fusions are targeted to virtually any compartment of the cell. In the case of insertions in previously known genes, we observe that the subcellular localization of the fusion protein corresponds to the described distribution of the endogenous protein. The artificial GFP exon does not disturb upstream and downstream splicing events. Many insertions correspond to genes not predicted by the Drosophila Genome Project. Our results show the feasibility of a protein trap in Drosophila. GFP reveals in real time the dynamics of protein's distribution in the whole, live organism and provides useful markers for a number of cellular structures and compartments.